Strengthening decision-making processes to address the climate challenge - Luisa Carpinelli; Daniele Franco (EconPol Forum, 2023)
In spite of the dramatic implications of current climate trends, global action to reach net-zero objectives remains inadequate. While the transition challenge is of an eminently technological and financial nature, the decision-making process is fundamental to effectively address climate issues, both at the national and international levels. It is crucial to transfer scientific information to the general public in a systematic way, not only on the risks of climate change but also on climate and compensation policies. This can increase acceptability of immediate climate action, whose benefits will be more evident in the future. The weight given to the future in the decision-making process should be strengthened through borrowing mechanisms from other fields, via legislation, procedures, and technical bodies In parallel, international coordination is fundamental. Voluntary UN level agreements are the ideal venue for cooperation, and should be pursued courageously, with the G20 in a leading position to aggregate political consensus. Climate clubs may represent a second-best solution that should be tested quickly.
Keywords: 330